The Natural Real Interest Rate and the Output Gap in the Euro Area: A Joint Estimation - Julien Garnier; Bjørn-Roger Wilhelmsen (Norges Bank, 2005)
The notion of a natural real rate of interest, due to Wicksell (1936), is widely used in current central bank research. The idea is that there exists a level at which the real interest rate would be compatible with output at its potential level and stationary inflation. Such a consept is of primary concern for monetary policy because it provides a benchmark for the monetary policy stance. This paper applies the method recently suggested by T. Laubach and J.C.Williams to jointly estimate the natural real interest rate and the output gap in the euro area using data from 1960. Our results suggest that the natural real rate of interest has declined gradually over the past 40 years. They also indicate that monetary policy in the euro area was on average stimulative during the 1960s and the 1970s, while it contributed to dampen the output gap and inflation in the 1980s and 1990s.
hdl:11250/2498430
Keywords: C32; E43; E52; O40; 330; Kalman filter; real interest rate gap; output gap; euro area